Identification and Classification of Face Emotions Based on Age and Linguistic approach Using Convolution Neural Network and Analytic Hierarchy Process - Dasharath.K.Bhadangkar, Jagadeesh D. Pujari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Face recognition has been an important topic of study for the last few decades. Human facial expressions show a lot of information instead of telling people what they are saying. It is important for people and machines to be able to recognise each other's faces. Computers still have a hard time figuring out how to recognise facial expressions with a high level of accuracy. In this paper we have used Convolution neural network (CNN) algorithm to recognise and classify face emotions based on age group. Then this paper focuses on Analytic hierarchy process (AHP) to recognise and classify face emotions based on linguistic approach.